2022
DOI: 10.20944/preprints202201.0137.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges of CRISPR-based Gene Editing in Primary T Cells

Abstract: Adaptive T cell immunotherapy holds great promise for the successful treatment of leukemia as well as other types of cancers. More recently, it was also shown to be an effective treatment option for chronic virus infections in immunosuppressed patients. Autologous or allogeneic T cells used for immunotherapy are usually genetically modified to express novel T cell or chimeric antigen receptors. The production of such cells was significantly simplified with the CRISPR/Cas system allowing deletion or insertion o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 156 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…According to the research on inhibitory receptors and immune checkpoint such as PD1, TGF beta and CTLA-4 important hallmarks of those in cancer treatment were found out. Inhibitory receptors (iRs) are important in function of adaptive immune cells and in T cell exhaustion which is a common event in cancer [38,39] by blocking checkpoint molecules re-establishing the potency of T cells is one important part in the cancer treatment process via immune-checkpoint therapy [40,41]. CRISPR is a good safeguarding tool to derange immune checkpoint by protecting from checkpoint inhibition via knock out immune checkpoint molecules in CAR T cells.…”
Section: How Crispr Is Used In Car T Cell Therapymentioning
confidence: 99%
“…According to the research on inhibitory receptors and immune checkpoint such as PD1, TGF beta and CTLA-4 important hallmarks of those in cancer treatment were found out. Inhibitory receptors (iRs) are important in function of adaptive immune cells and in T cell exhaustion which is a common event in cancer [38,39] by blocking checkpoint molecules re-establishing the potency of T cells is one important part in the cancer treatment process via immune-checkpoint therapy [40,41]. CRISPR is a good safeguarding tool to derange immune checkpoint by protecting from checkpoint inhibition via knock out immune checkpoint molecules in CAR T cells.…”
Section: How Crispr Is Used In Car T Cell Therapymentioning
confidence: 99%
“…In conclusion, the overall efficiency of knock-in seems to remain lower than the knockout efficiency, using CRISPR-Cas9. Moreover, delivery of CRISPR-Cas9 through viral vectors requires in vitro T cell activation and culture [41,42]. However, the use of electroporation (EP) methods to deliver Cas9-gRNA protein complex in knockout studies demonstrated the potential to overcome this issue and to achieve gene editing without in vitro T cell activation [42,43].…”
Section: Talens Crispr/casmentioning
confidence: 99%
“…For autologous CAR-T, this incorporates trouble getting expansive numbers of T cells from patients that are lymphopenic due to other medicines and long timeframes for creating an adequate restorative measurements [65].For allogeneic CAR-T, the solid donor-derived cells can be rejected by the understanding resistant framework, cause harmfulness, or initiate GvHD [66]. Shockingly, a few cancers are able to maintain a strategic distance from pulverization by CAR-T cells by overexpressing certain proteins, like modified cell passing protein 1 (PD-1), on their surface [67] .CRISPR-Cas9 quality altering has expanded the security and viability of CAR-T cell therapies in an assortment of ways [68] .Firstly, CRISPR can be utilized to thump within the CAR in a focused on way -for illustration, to a safe harbor location within the genome -to guarantee adequate, long-term expression of the receptor on the cell surface [69] .Furthermore, CRISPR can thump out certain qualities in CAR-T cells to extend their cancerkilling movement .Thirdly, it can be utilized to form alters that minimize CAR-T cell fatigue and increment their long-term multiplication [70].At long last, CRISPR alters can be utilized to produce all inclusive, 'off-the-shelf' CAR-T cells from actuated pluripotent stem cells (iPSCs), invalidating collecting confinements, long hold up times, and harmfulness issues [71] .…”
Section: Til and Tcr Cell Therapiesmentioning
confidence: 99%